1999
DOI: 10.1007/bf02235043
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of rectovaginal fistula with sphincter disruption by combining rectal mucosal advancement flap and anal sphincteroplasty

Abstract: The combination of mucosal advancement flap and anal sphincteroplasty is a safe and highly effective procedure for correcting rectovaginal fistula with sphincter disruption after obstetrical injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 17 publications
0
22
0
2
Order By: Relevance
“…This can be accomplished with either a rectal advancement flap performed in concurrence with an anterior sphincteroplasty [31] or as the case at our institution, an episioproctotomy is performed [32] . An episioproctotomy entails performing a fistulotomy and creating of a defect similar to a fourth degree perineal laceration during vaginal childbirth [32] .…”
Section: Transperineal Approachesmentioning
confidence: 99%
“…This can be accomplished with either a rectal advancement flap performed in concurrence with an anterior sphincteroplasty [31] or as the case at our institution, an episioproctotomy is performed [32] . An episioproctotomy entails performing a fistulotomy and creating of a defect similar to a fourth degree perineal laceration during vaginal childbirth [32] .…”
Section: Transperineal Approachesmentioning
confidence: 99%
“…Success rates have ranged from 74 to 95 % [ 37 , 64 -66 ]. In a series where all 20 patients had mucosal fl aps in addition to sphincteroplasties, Khanduja et al reported that drainage of stool and fl atus stopped in all, and 14 had perfect continence while six reported their continence was improved [ 67 ].…”
Section: Rectovaginal Fistulamentioning
confidence: 99%
“…Sphincteroplasty can, in many cases, be done in conjunction with fistula repair (e.g., a high rectal vaginal fistula after a fourth-degree tear) [43]. Here, the sphincter repair will act as a "buttress" to help facilitate healing of the fistula.…”
Section: Sphincteroplastymentioning
confidence: 99%